On similarity of various reactor spectra and 235U prompt fission neutron spectrum. (May 2018) - Košťál, Michal; Matěj, Zdeněk; Losa, Evžen; Huml, Ondřej; Štefánik, Milan; Cvachovec, František; Schulc, Martin; Jánský, Bohumil; Novák, Evžen; Harutyunyan, Davit; Rypar, Vojtěch
Abstract: A well-defined neutron spectrum is an essential tool not only for calibration and testing of neutron detectors used in dosimetry and spectroscopy but also for validation and verification of evaluated cross sections. A new evaluation of thermal-neutron induced 235 U PFNS was performed by the International Atomic Energy Agency (IAEA) in the CIELO (Collaborative International Evaluated Library Organisation Project) project; new measurements of Spectral Averaged Cross sections averaged in the evaluated spectrum are to be obtained. In general, a neutron spectrum in the core is not identical to the pure fission one because fission neutrons undergo many scattering reactions, but it can be shown that PFNS and reactor spectra become undistinguishable from a certain energy boundary. This limit is important for experiments, because when the studied reaction threshold is over this limit, the spectral averaged cross sections in PFNS can be derived from the measured reactions in the reactor core. The evaluation of the neutron spectrum measurements in three different thermal-reactor cores shows that this lower limit is around the energy of 5.5 – 6 MeV. Above this energy the reactor spectra becomes identical with the 235 U PFNS. IAEA CIELO PFNS is within 5% of the measured PFNS from 10 to 14 MeV in a LR-0 reactor, while ENDF/B-VII evaluated PFNS underestimated measured neutron spectra. Highlights: Neutron spectra in LR-0, VR-1 and AKR-2 reactors. Comparison of the experimental data with calculation. Share of reflections in VR-1 beam. Similarity of reactor spectra with 235 U PFNS.